Antibody treatment of hepatocellular carcinoma: a review of current and emerging approaches - El-Kafrawy, Sherif A.; Elkafrawy, Mostafa S.; Azhar, Esam I.; Saeed, Anwaar; Tabll, Ashraf A. (Frontiers in Immunology, 2025)
Hepatocellular carcinoma (HCC) remains a leading cause of cancer-related deaths worldwide, underscoring the urgent need for innovative therapeutic strategies. Antibody-based therapies have emerged as a transformative approach, offering specificity and the potential to overcome the limitations of traditional treatments. This comprehensive review evaluates the current and emerging applications of antibody therapies in HCC, including monoclonal antibodies (mAbs), bispecific antibodies, and antibody-drug conjugates (ADCs). It explores their mechanisms of action, such as immune modulation, angiogenesis inhibition, and targeted cytotoxicity. Key advancements include the integration of immune checkpoint inhibitors (ICIs) like PD-1/PD-L1 and CTLA-4 inhibitors into clinical practice and the development of bispecific antibodies and ADCs targeting tumor-specific antigens like glypican-3. While these therapies have shown promise in improving patient outcomes, challenges such as tumor heterogeneity, resistance mechanisms, and immune-related adverse events persist. This review highlights recent clinical trial data, identifies areas for future research, and emphasizes the potential of combining antibody therapies with other modalities to enhance efficacy and overcome therapeutic barriers. By addressing these challenges and leveraging advancements in antibody engineering and biomarker discovery, antibody-based therapies hold significant promise for revolutionizing the treatment paradigm for HCC.